Answer:
y = -1, x = -2
Step-by-step explanation:
First, multiply the top equation by 2 to make 3x become 6x:
6x - 8y = -4
Second, multiply the bottom equation by 3 to make -2x become -6x:
9y - 6x = 3
Add the two equations together, and you get:
y = -1
Plug in y as -1 into the first or second equation:
3x - 4(-1) = -2
OR
3(-1) - 2x = 1
x = -2
The opposite angles equal each other, so X and Z are equal
using that we solve for x by setting them equal:
6x-60 = 2x+68
subtract 2x from each side:
4x -60 = 68
add 60 to each side:
4x = 128
divide both sides by 4
x = 128/4
x = 32
now we know x so we can solve everything else by replacing x with 32
WY = 3x+5 = 3(32)+5 = 96+5 = 101
angle Z = 2x+68 = 2(32)+68 = 64+132
the answer is C
Answer:
38.88
Step-by-step explanation:
72% of 54
=
× 54
= 0.72 × 54
= 38.88
The mean is 21. The median is 15. The mode is 15. The range is 16.
Multiply straight across
5/1 * 3/4 = 15/4
now change it into a mixed number
3 3/4